THE MEANING OF THE REBA RITUAL IN THE BHAJAWA ETHNICFARMING COMMUNITY OF JAWA MEZE VILLAGE,BAJAWA DISTRICT, NGADA REGENCY: MAKNA RITUAL REBA PADA MASYARAKAT PETANI ETNIK BHAJAWA KELURAHAN JAWA MEZE KECAMATAN BAJAWA KABUPATEN NGADA - Nong Hoban; Fransiskus Savion Eo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The problem addressed in this study is the meaning of the Reba ritual among the Bhajawa ethnic farming community in Jawa Meze Village, Bajawa District, Ngada Regency. The objective of this study is to identify the meaning of the Reba ritual within the Bhajawa ethnic farming community. This study employed a qualitative research method. Data were collected through interviews, observations, and documentation, while data analysis consisted of data reduction, data presentation, and conclusion drawing. The findings reveal that the Reba ritual embodies several meanings: (1) the preservation of tradition and social dynamics, reflecting customary norms that regulate community life; (2) a religious meaning, expressing devotion to the Transcendent Being and ancestors; (3) a historical meaning, preserving past experiences as guidance for present and future life; (4) a political meaning, reflecting authority, leadership, and social cohesion within the clan structure; and (5) an aesthetic meaning, demonstrated through metaphorical language, ritual discourse, and the rhythm of tandak o uwi. These findings imply that the Reba ritual plays a vital role in preserving the cultural identity, social values, and traditional heritage of the Bhajawa ethnic community.